Prostituição e morte em Maggie: a girl of the streets: uma leitura feminista sobre a Slum fiction norte-americana de Stephen Crane - Conde, Adriana Carvalho [UNESP] (2014)
The thesis examines the image of the prostitute in Maggie: A Girl Of The Streets of Stephen Crane, published in 1896 focusing the concepts of feminist criticizes assumed to read and interpret the character Maggie Johnson. It reading from the female experience of interpretation, giving new meaning with this new reading. We assume that the character follows models of representation of women, traditionally widespreaded in the literature, especially in naturalistic works. They elect a fallen woman as the protagonist of several stories of degradation and death. Through the study on women prostitutes in the literature, we were able to reflect on the condition of women in the nineteenth century, noting the inability of the character to integrate socially, among other problems caused by life experiences that degraded. Resident of slums is portrayed by Crane in a wild and degrading environment, in this case, the city of New York, in full industrial development. Despite being the protagonist character, the author highlights the fragile and naive aspect of the character, presenting it as if it was morally and intellectually inferior, unable to act against the already predetermined fate, with a critical situation of working women in that context. We know that the author takes an antagonistic stance of his predecessors, romantics, and, therefore, characterizes Maggie emphasizing romantic concepts in building character, in order to oppose the ideological and formal rules of Romanticism. A key feature of Crane's irony in this story, which conditions are more revealing conflicting moral values, similarly conflicting. We analyze the representation of women in marginal literature and seek to clarify some stereotypes that served to represent the woman